Environmental perturbations at the early Eocene ETM2, H2, and I1 events as inferred by Tethyan calcareous plankton (Terche section, northeastern Italy). (17th September 2016) - D'Onofrio, Roberta; Luciani, Valeria; Fornaciari, Eliana; Giusberti, Luca; Boscolo Galazzo, Flavia; Dallanave, Edoardo; Westerhold, Thomas; Sprovieri, Mario; Telch, Sonia
Abstract: Several early Eocene hyperthermals have been recently investigated and characterized in terms of temperature anomalies and oceanographic changes. The effects of these climatic perturbations on biotic communities are much less constrained. Here we present new records from the Terche section (northeastern Italy) that, for the first time, integrates data on planktic foraminifera and calcareous nannofossils across three post‐Paleocene‐Eocene Thermal Maximum negative carbon isotope excursions (CIEs). The biomagnetostratigraphic framework generated at Terche allows us to confidently relate such CIEs to the Eocene Thermal Maximum 2 (ETM2), H2, and I1 events. Each of these events coincides with lithological anomalies characterized by significantly lower calcium carbonate content (marly units, MUs). We interpret these MUs as mainly linked to an effect of increased terrigenous dilution, as dissolution proxies do not display significant variations. Calcareous plankton assemblages change significantly across these events and radiolarians increase. Observed changes suggest that transient warming and environmental perturbations, though more intense during ETM2, occurred during each of the three investigated perturbations. Variations among calcareous plankton suggest increase in surface‐water eutrophication with respect to the pre‐event conditions, coupled with a weakening of the upper water‐column thermal stratification. Higher nutrient discharge was related to intensification of the hydrological cycle as a consequence of the warmer climate. These conditions persisted during the early CIE recovery, implying slower recovery rates for the environment and biota than for the carbon cycle. Key Points: Biotic changes, eutrophy, and weakening of water thermal stratification were more marked for ETM2 Terrigenous dilution is linked to strengthening of hydrological cycle and enhanced weathering Biotic changes and environmental perturbations persisted during carbon isotope excursion recovery